Does Travel Broaden the Mind? Breadth of Foreign Experiences Increases Generalized Trust. (July 2014) - Cao, Jiyin; Galinsky, Adam D.; Maddux, William W.
Five studies examined the effect of breadth and depth of foreign experiences on generalized trust. Study 1 found that the breadth (number of countries traveled) but not the depth (amount of time spent traveling) of foreign travel experiences predicted trust behavior in a decision-making game. Studies 2 and 3 established a causal effect on generalized trust by experimentally manipulating a focus on the breadth versus depth of foreign experiences. Study 4 used a longitudinal design to establish that broad foreign travel experiences increased generalized trust. Study 5 explored the underlying processes and found that a focus on the differences rather than the similarities among the countries visited was critical in producing greater generalized trust. Across five studies, using various methods (correlational, lab experiment, and longitudinal), samples (United States and Chinese) and operationalizations (trust game and generalized trust scale), we found a robust relationship between the breadth of foreign travel experiences and generalized trust.